Evaluating the impact of patient blood management implementation: a protocol for a quasiexperimental study in a Portuguese tertiary care setting - João Firmino-Machado; Diana Castro Paupério; Henrique Coelho; Sandrine Jorge; Guilherme Rabello; Donat R Sphan (BMJ Open)
Introduction Patient blood management (PBM), an evidence-based, patient-centred approach for optimising blood health, faces significant implementation challenges despite regulatory support, and this study explores its adoption within a Portuguese hospital to enhance education, develop tailored protocols and address healthcare system complexities, thereby contributing a unique perspective to the global discourse on PBM in Portuguese-speaking countries. This study will evaluate the clinical outcomes and cost-effectiveness of implementing a PBM programme in elective surgical patients at a tertiary Portuguese hospital, with secondary objectives focusing on preoperative anaemia prevalence and aetiology, PBM protocol adherence, transfusion practices guided by viscoelastic tests and the impact of cell salvage techniques.Methods A baseline evaluation will be conducted in 2018, and postintervention assessments will follow from 2019 to 2024. The control group comprised patients who underwent selected elective surgeries—including cardiac, general, orthopaedic, urological and gynaecological procedures—during 2018 without exposure to targeted PBM interventions. The intervention group consisted of patients scheduled for the same elective surgeries, who were referred for preanaesthesia evaluation to identify the need for PBM interventions. These interventions, where indicated, were implemented during the preoperative phase and extended to the intraoperative and postoperative periods to ensure a comprehensive and standardised approach to PBM application. Data will be extracted from pseudoanonymised medical records, ensuring full compliance with ethical standards and data protection regulations. Statistical analyses will be performed using robust methods suitable for categorical and continuous variables, enabling the evaluation of temporal trends and the overall effectiveness of PBM interventions in improving clinical outcomes.Ethics and dissemination Our research has been ethically approved by the Vila Nova de Gaia/Espinho Hospital Centre’s Ethical Health Committee (approval number 196/2023–1). We plan to disseminate our findings through posters, lectures at conferences and in scientific journals.